Investigation of the Ternary System, Water/Hydrochloric Acid/Polyamide 66, for the Production of Polymeric Membranes by Phase Inversion - Jocelei Duarte; Camila Suliani Raota; Camila Baldasso; Venina dos Santos; Mara Zeni (Membranes)
The starting point for the preparation of polymeric membranes by phase inversion is having a thermodynamically stable solution. Ternary diagrams for the polymer, solvent, and non-solvent can predict this stability by identifying the phase separation and describing the thermodynamic behavior of the membrane formation process. Given the lack of data for the ternary system water (H2O)/hydrochloric acid (HCℓ)/polyamide 66 (PA66), this work employed the Flory–Huggins theory for the construction of the ternary diagrams (H2O/HCℓ/PA66 and H2O/formic acid (FA)/PA66) by comparing the experimental data with theoretical predictions. Pure polymer and the membranes produced by phase inversion were characterized to provide the information required to create the ternary diagrams. PA66/FA and PA66/HCℓ solutions were also evaluated regarding their classification as true solutions, and the universal quasi-chemical functional group activity coefficient (UNIFAC) method was used for determining non-solvent/solvent interaction parameters (g12). Swelling measurements determined the polymer/non-solvent interaction parameter (χ13) for H2O/PA66 and the solvent/polymer interaction parameter (χ23) for PA66/FA and PA66/HCℓ. The theoretical cloud point curve was calculated based on “Boom’s LCP Correlation” and compared to the curve of the experimental cloud point. The ternary Gibbs free energy of mixing and χ23 indicated FA as the best solvent for the PA66. However, for HCℓ, the lower concentration (37–38%), volatility, and fraction volume of dissolved PA66 (ϕ3) indicated that HCℓ is also adequate for PA66 solubilization based on the similar membrane morphology observed when compared to the PA66/FA membrane.